ANXIETY ASPECT OF THE MAIN CHARACTER IN THE NOVEL IF I WAS YOUR GIRL BY MEREDITH RUSSO - Janita Rahma Mayestika; Henny Suharyati; Agnes Setyowati H (Universitas Pakuan, 2019)
Abstract The purpose of this thesis is to analyze the anxiety that has been experienced by the main character from the novel If I Was Your Girl by Meredith Russo. Through the analytical descriptive method and supported with psychoanalysis theory, the present writer also concludes that the main character has experienced the anxiety, which gives the influence in her social life. This anxiety is influenced by the internal and external factors. Two differences background which affected are sexual disorder behavior of the main character and harsh environment which made the main character has experienced the anxiety as long as her life. That matter also influences the character’s psychology. The anxiety effect gives too much mental pressure to the main character. Keywords: Anxiety, Main Character, Psychoanalysis, Transgender